DRIFTS Studies and Quantification of Water uptake experiments onto Iron(II) fumarate, Polyguaiacol and Polycatechol particles. - Mohammad Aminur Rahman (Journal of Science, 2026)
This research investigates the hygroscopic properties of organic and organometallic polymeric particles, namely Iron(II) fumarate, Polyguaiacol, and Polycatechol. These particles are efficiently formed in iron-catalyzed reactions with aromatic and aliphatic dicarboxylic acid compounds which were detected in field-collected Secondary Organic Aerosol (SOA). The structure of surface water was studied using diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). Spectroscopic data show that water bonding with organic functional groups acting as hydrogen bond acceptors causes shifts in their vibrational modes. Analysis of the hydroxyl group stretching region revealed weak and strong hydrogen bonding networks that suggest cluster formation reflecting water-water and water-organics interactions, respectively. A modified Type II multilayer Brunauer Emmett-Teller (BET) adsorption model described the adsorption isotherm on the materials, Fe fumarate, polycatechol, and polyguaiacol. Modified BET analysis shows that multilayer adsorption takes place for model organic compounds.